The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1088/1755-1315/61/1/012140
|View full text |Cite
|
Sign up to set email alerts
|

Density and hardness of Nd-doped zircon ceramics as nuclear waste forms

Abstract: Abstract. Zircon ceramics were employed as host material for immobilization of element Nd, which was used as the surrogate of trivalent actinide nuclide. A series of Zr 2-x Nd x Si 2 O 8-0.5x compounds were prepared by solid-state reaction method at 1500 ℃ for 72 h in air and investigated in respect of their physics performances. These performances were characterized by density and hardness. The results show that the density raises as the value of x increases from 0.02 to 0.20. Moreover, the hardness of the Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…3(b) and 3(h), respectively [17][18][19]. The result from our study is consistent with Yuan et al [20], which reported the increase in hardness with increasing density. The temperature dependences of the dielectric constant and dielectric loss of the BCT-NBT ceramics at various sintering temperatures with 1 kHz frequency at Curie temperature and room temperature were studied as shown in Table 2 and plotted in Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3(b) and 3(h), respectively [17][18][19]. The result from our study is consistent with Yuan et al [20], which reported the increase in hardness with increasing density. The temperature dependences of the dielectric constant and dielectric loss of the BCT-NBT ceramics at various sintering temperatures with 1 kHz frequency at Curie temperature and room temperature were studied as shown in Table 2 and plotted in Fig.…”
Section: Resultssupporting
confidence: 92%
“…This result confirmed that the improvement in the Vickers and Knoop micro-hardness could be related to the change in fracture mode from partial intra-granular to mainly intra-granular as shown in Fig.3(b) and 3(h), respectively[17][18][19]. The result from our study is consistent with Yuan et al[20], which reported the increase in hardness with increasing density.…”
supporting
confidence: 92%
“…3 Data reported in Smedskjaer et al (2008). 4 Data reported in Yuan et al (2017) 5 Data reported in Dekker and Rieck (1974). The reported data are averaged from the applied load at [110] and [100].…”
Section: Code Availabilitymentioning
confidence: 99%